جهود الإمامين "البخاري ومسلم" في إبراز مكانة الصحابة وفضائلهم في الصحيحين: الخلفاء الأربعة أنموذجا: دراسة تحليلية - الفقيه، شفاء علي (جامعة آل البيت, 2020)
تناولت هذه الدراسة التعريف بجهود الإمامين (البخاري ومسلم) في إخراج الأحاديث الصحيحة التي اختصت بفضائل الصحابة ومناقبهم من خلال تحليل ما أخرجا من أحاديث، وقد خلصت الدراسة إلى نتائج منها؛ دقة منهج الإمامين البخاري ومسلم في انتقاء الأحاديث النبوية الصحيحة التي كشفا من خلالها عن مكانة الصحابة وجهودهم التي خدموا بها رسالة الإسلام وقدموا في سبيلها التضحيات العظيمة، كما أظهرت حسن الصناعة الحديثية في التبويب وإخراج المرويات التيرد بها على عدد من الشبهات الزائفة التي أثارها أعداء الإسلام ضد الصحابة. وأظهرت ضرورة الاهتمام بما أورده الشيخان من أحاديث حول الصحابة؛ لأنها تعد مصدرا من المصادر المهمة التي لا يستغني عنها أي باحث منافح عن الصحابة، وبخاصة الخلفاء الراشدين.
This study shows the efforts of the imams (Bukhari and Muslim) in realization the Sahih hadiths, which specialized in the virtues of the companions through analyzing what they had narrated of Ahadith. The study concluded results such as; the accuracy of the methods of the imams Bukhari and Muslim in the selection of the Sahih Hadiths, which revealed the status of the companions and their efforts, which served the message of Islam and made great sacrifices in its way. The study also showed the well Hadith skillfulness at tabulation and classification, which turned away a number of false suspicions raised by the enemies of Islam against the companions. The study affirm the need to pay attention to what the two Imams (Bukhari and Muslim) had mentioned about Sahaba because it is one of the most important sources, which is contained to the false and fabricated accounts that have spread in many historical books and many works, and any researcher cannot dispense these significant books to defend the companions, especially the Righteous Caliphs.
Keywords: الأحاديث النبوية -- الصحابة -- فضائل الصحابة -- الخلفاء الراشدين -- كتب الحديث -- صحيح البخاري -- صحيح مسلم -- الإمام البخاري -- الإمام مسلم